The importance of dynamics in integrative modeling of supramolecular assemblies. (April 2015) - Tamò, Giorgio E; Abriata, Luciano A; Dal Peraro, Matteo
Highlights: Integrative modeling is effective to reveal the structure of macromolecular assemblies. Supramolecular assembly often involves multiple dynamic functional states. Dynamics of individual subunits is key and needs to be included in model building. Abstract : Revealing the atomistic architecture of supramolecular complexes is a fundamental step toward a deeper understanding of cellular functioning. To date, this formidable task is facilitated by an emerging array of integrative modeling approaches that combine experimental data from different sources. One major challenge these methods have to face is the treatment of the dynamic rearrangements of the individual subunits upon assembly. While this flexibility can be sampled at different levels, integrating native dynamic determinants with available experimental inputs can provide an effective way to reveal the molecular recognition mechanisms at the basis of supramolecular assembly.